Synthesis, characterization, and application of chiral Schiff-base complexes - Oshin, Kayode (Kansas State University, 2011)
This work examines the synthesis of novel chiral Schiff-base complexes derived from (1R,2R)-cyclohexanediamine and (R)-[1,1’-binaphthalene]-2-2’-diamine structural backbones with quinoline, isopropyl-quinoline, and benzoquinoline structural side-arms. We incorporated some degree of flexibility in the ligands and complexes so they can accommodate the sterics of different substrates during a catalytic reaction. We successfully achieved this by reducing the imine bond in the ligands to the corresponding amine bond. Therefore, the successful reduction and metallation of some of these ligands to give structures of different symmetries is reported. We had difficulty reducing ligands with the binaphthalene backbone but were able to partially reduce the ligand through a one-pot reaction with a zinc(II) salt and NaBH4. The complete 1H NMR assignments of the complexes reported in this thesis serve as a valuable tool for use in the characterization of future complexes. The complete NMR characterization of compounds reported is a complex process because they are polycyclic aromatic systems and the coupling network similarity in different parts of the molecule usually results in severe overlap of their 1H resonances. To overcome this impediment, we took advantage of various 2D-NMR techniques (COSY, NOESY, ROSEY, HSQC, and HMBC) along with other 1D-NMR experiments (1H HOMODEC, 1H, and 13C) to completely assign the desired complexes. Subsequently we also studied the coordination chemistry of several meal cations with our ligand system with the goal of obtaining single stranded monhelices. The potential use of some of the complexes in the area of NMR discrimination and kinetic resolution of racemic mixtures was examined and shown to be promising. Several NMR experiments were conducted using the racemic olefins 3-buten-2-ol and 1-penten-3-ol to demonstrate the discriminating power of our silver(I) complexes. We discovered that sterics play an important role in this resolution experiment and the bulky nature of our complexes affect the overall efficiency of the NMR discriminatory process as it diminishes the contact between the reactive metal center and the olefins involved. Temperature also plays a vital role in the chiral recognition of racemic olefins as we examined the ideal temperature needed to reduce the various dynamic processes that take place in solution at room temperature.
Keywords: Chemistry; Inorganic; Chiral; Schiff-Base; Chemistry (0485)